Pahang melioidosis registry - How, Soon Hin; Ng, Teck Han; Ab Rahman, Jamalludin; Tee, Hoi-Poh; Kuan, Yeh Chunn; Alex, Francis; Che Ahmad, Aminudin; Satwi, Sapari; Haque, Quazi Manjurul (Malaysian Medical Associations, 2009)
Melioidosis has a high annual incidence and mortality rate in Pahang, Malaysia. We initiated the first melioidosis registry in the country on 1st July 2005 to improve the management of melioidosis in the state. Continuous medical education on melioidosis was carried out in all hospitals in the state to highlight the magnitude of the disease and to educate the doctors on the treatment of the disease. All culture confirmed cases were registered and analysed. During the one-year study period from 1st July 2005 till 30th June 2006, a total of 63 patients had positive culture for Burkholderia pseudomallei. The calculated annual incidence of melioidosis in Pahang state was 4.3 per 100,000 population per year (Adult, 6.0 per 100, 000 population per year and paediatric, 1.6 per 100,000 population per year). There were 55 Malays (87.3%), three Chinese (4.8%), four aborigines (6.3%) and one Indonesian. Nine (14.3%) were less than 18 years old. The median age was 49 years (range: 1-68 years). Only one patient (1.6%) had a previous history of confirmed melioidosis. With this programme, we had observed a decline in adult mortality from 54% to 44%, although this was not statistically significant. However, culture-confirmed relapses had dropped from 19% to nil. Several measures need to be taken to decrease mortality from melioidosis in endemic countries.